Aberrant MHC class II expression in mouse joints leads to arthritis with extraarticular manifestations similar to rheumatoid arthritis - Kanazawa, Satoshi (National Academy of Sciences, 2006)
Genetic susceptibility to rheumatoid arthritis (RA) is associated with certain MHC class II molecules. To clarify the role of these determinants in RA, we generated the D1CC transgenic mouse that expressed genes involved in antigen processing and presentation by the MHC class II pathway in joints. The class II transactivator, which was transcribed from the rat collagen type II promoter and enhancer, directed the expression of these genes. In D1CC mice congenic for the H-2(q) (DBA/1) background, small amounts of bovine collagen type II in adjuvant induced reproducibly an inflammatory arthritis resembling RA. Importantly, these stimuli had no effect in DBA/1 mice. Eighty-nine percent of D1CC mice developed chronic disease with joint swelling, redness, and heat in association with synovial proliferation as well as pannus formation and mononuclear infiltration of synovial membranes. Granulomatous lesions resembling rheumatoid nodules and interstitial pneumonitis also were observed. As in patients with RA, anticyclic citrullinated peptide antibodies were detected during the inflammatory stage. Finally, joints in D1CC mice displayed juxtaarticular demineralization, severe joint space narrowing, and erosions, which led to ankylosis, but without the appearance of osteophytes. Thus, aberrant expression of MHC class II in joints facilitates the development of severe erosive inflammatory polyarthritis, which is very similar to RA.